2023
DOI: 10.2174/0115672026267629230920062917
|View full text |Cite
|
Sign up to set email alerts
|

Smurf2-Mediated Ubiquitination of FOXO4 Regulates Oxygen-glucose Deprivation/Reperfusion-induced Pyroptosis of Cortical Neurons

Bin Yan,
Yan Jin,
Song Mao
et al.

Abstract: Background: Smad ubiquitination regulatory factor 2 (Smurf2) has been observed to alleviate ischemia-reperfusion injury. This study sought to explore the molecular mechanism of Smurf2-mediated forkhead box O4 (FOXO4) ubiquitination in oxygen-glucose deprivation/ reperfusion (OGD/R)-induced pyroptosis of cortical neurons. Methods: Human cortical neurons (HCN-2) were subjected to OGD/R to establish a cell model of cerebral stroke. Smurf2, FOXO4, and doublecortin domain containing 2 (DCDC2) expressions were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Previous studies have shown that FOXO4 is highly expressed during IRI in the liver (9), kidney (5) and heart (22). In addition, FOXO4 is expressed in OGD/R-treated human cortical neurons, suggesting that FOXO4 may participate in cerebral stroke (23). To the best of our knowledge, the present study is the first to demonstrate that FOXO4 expression is abnormally elevated in OGD/R-induced HCMEC/D3 cells.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have shown that FOXO4 is highly expressed during IRI in the liver (9), kidney (5) and heart (22). In addition, FOXO4 is expressed in OGD/R-treated human cortical neurons, suggesting that FOXO4 may participate in cerebral stroke (23). To the best of our knowledge, the present study is the first to demonstrate that FOXO4 expression is abnormally elevated in OGD/R-induced HCMEC/D3 cells.…”
Section: Discussionsupporting
confidence: 49%